Introduction to continuum mechanics - Lai, W. Michael, 1930- (Butterworth-Heinemann, 1996)
Continuum mechanics studies the response of materials to different loading conditions. The concept of tensors is introduced through the idea of linear transformation, and the interrelation of direct notation, indicial notation, and matrix operations is also presented. A wide range of idealized materials are considered through simple static and dynamic problems.
Previously printed by: Pergamon Press, 1993.
Keywords: Continuum mechanics.; elektronické knihy; electronic books